A STUDY OF TEACHER TALK IN INTERACTIONS INEFL CLASSES - markus deli girik allo (Teaching English as a Foreign Language Overseas Journal, 2016)
Teacher talk plays an important role in provoking interactions between teachersand students. Therefore, lecturers should try to understand what languages wouldbe more efficient in creating an environment in which students feel morecomfortable and more confident and become more involved in interactiveactivities in the language classroom. This study investigated kinds of teacher talkby lecturers and the most employed of kinds of teacher talk by the lecturers inteaching English. It was found that: the kinds of teacher talk by lecturers are:Initiation such as: questioning, invitation, and direction, follow up in term of to noand incorrect answer such as: inform, prompt, encouragement, criticizing, andignoring, follow up in term of to correct answer such as: acknowledgement, andcomment. In ways of initiation, questioning (65%) as the most employed by thelecturers. In term of follow up in purpose to no and incorrect answer, inform(30%) as the most employed, and in purpose to correct answer, acknowledgement(60%) as the most employed by the lecturers.